Alternative Medicine - Sakagami, Hiroshi (IntechOpen, 2012)
Alternative medicine is recognized as medical products and practices that do not belong to the standard cares taken by medical doctors, doctors of osteopathy and allied health professionals. It has developed into a multitude of medical products and practices that significantly improve the body condition and show disease prevention actions. The content of this book does not cover all areas of alternative medicine, but provides the reader with insights into selected aspects of established and new therapies. It consists of 12 chapters that are separated into 4 parts: (1) Historical and Cultural Perception, (2) Compositional Analysis, (3) Therapeutic Potential, and (4) Action Mechanism and Future Direction, written by world experts who are reviewing their original and others' research. The book will be useful to students, clinicians, teachers and researchers who have interest in advances in alternative medicines.